A Semiotic Analysis and Cultural Values in the Lyrics of the Sumbawa Song "Poto Tano" - Kencana, Dwi Sekar Sari (Abjad Journal of Humanities & Education, 2025)
This study aims to analyse the semiotic meaning and cultural values ​​contained in the lyrics of the Sumbawa song "Poto Tano" by Ace Let Luar, which is popularized by Yuni Shara. The approach used is Ferdinand de Saussure's semiotic theory to identify the elements of the signifier and signified, and Clifford Geertz's interpretive anthropology theory to explore the cultural values ​​of the Sumbawa people. This study uses a qualitative descriptive method with primary data in the form of song lyrics and secondary data from journals, books, and internet sources. The results of the analysis show that the lyrics of "Poto Tano" represent various symbolic meanings and cultural values, such as local patriotism, the values ​​of maritime community life, spirituality, traditional art expressions, social and family relationships, as well as hope and optimism. This song not only describes the natural beauty of Sumbawa, but also functions as a medium to preserve the cultural identity of the Sumbawa people in facing the challenges of modernization. The song "Poto Tano" has succeeded in becoming a cultural mirror that conveys a profound message about the life of the Sumbawa people while inviting the younger generation to appreciate and preserve local cultural heritage.